Efeito da idade na memória episódica: uma análise através dos paradigmas “que-onde-quando” e “que-onde-qual contexto” - Silva, Joenilton Saturnino Cazé da (2016)
Human aging causes different decline in many cognitive function. Episodic processing, among all memory systems, shows to be the most affected along aging. The episodic memory is a subsystem of memory responsible for receiving and storing information about certain episodes or events, temporally dated, high lighting a spatiotemporal relationship between them. One way of assessing this construct would be using behavioral criteria for identifying information about what happening, where and when, which are the basic components of “What-Where-When” paradigm, or else, by proposing to replace the temporal component by context, “What-Where-Which” paradigm. Thus, the objective of this research was to analyze the effect of aging on episodic memory, assessed by two experimental paradigms, to study the correlation of these tests with classic measures of episodic memory. We used a sample with 70 volunteers, divided in two group: younger (N = 35, M = 22,74; SD= 2,99) and older (N = 35, M = 62,54; SD = 4,82) adults. The evaluation protocol was composed of: (i) test based on the paradigm "What-Where-When"; (ii) test based on the paradigm "What-Where-Which"; (iii) classic episodic memory tests; and (iv) a neuropsychological battery, the latter being applied only to the elderly group. The results showed that different episodic memory task apparently measuring something in common. Comparisons between group showed effective impairment associated with aging for all aspects evaluated by the test "What-Where-When", and the integration aspect was the component that suffered the greatest decline associated with age [F(1, 68)= 53,86; p < .001; η² = .442]. Other results showed that Free Recall also presented decline [F(1, 68)= 18,60; p < .001; η² = .215]. However, it was not found significant differences between groups for the task based on the paradigm "What-Where-Which". The findings of this study show that task-based paradigm "What-Where-When" and "What-Where-Which" are promising instruments for measurement of episodic memory. However, apparently the temporal aspect was more sensitive to detect possible changes related to age.